Socioeconomic vulnerability associated to Toxoplasma gondii exposure in southern Brazil - Mareze, Marcelle; Benitez, Aline do Nascimento [UNESP]; Drulla Brandao, Ana Perola; Pinto-Ferreira, Fernanda; Miura, Ana Carolina; Cardoso Martins, Felippe Danyel; Caldart, Eloiza Teles; Biondo, Alexander Welker; Freire, Roberta Lemos; Mitsuka-Bregano, Regina; Navarro, Italmar Teodorico (Public Library Science, 2019)
Human toxoplasmosis, a protozoonosis caused by Toxoplasma gondii, has been described as a worldwide foodborne disease with important public health impact. Despite infection has reportedly varied due to differences in alimentary, cultural and hygienic habits and geographic region, social vulnerability influence on toxoplasmosis distribution remains to be fully established. Accordingly, the present study has aimed to assess T. gondii seroprevalence and factors associated to social vulnerability for infection in households of Ivaipora, southern Brazil, with 33.6% population making half minimum wage or less, ranked 1,055th in population (31,816 habitants), 1,406th in per capita income (U$ 211.80 per month) and 1,021st in HDI (0.764) out of 5,570 Brazilian cities. Serum samples and epidemiological questionnaires were obtained from citizen volunteers with official City Secretary of Health assistance in 2015 and 2016. In overall, serosurvey has revealed 526/715 (73.57%) positive samples for anti-T. gondii antibodies by Indirect Fluorescent Antibody Test. Logistic regression has shown a significant increase associated to adults (p = 0.021) and elderly (p = 0.014) people, illiterates (p = 0.025), unemployment (p < 0.001) and lack of household water tank (p = 0.039). On the other hand, sex (male or female), living area (urban or rural), yard hygiene, meat ingestion, sand or land contact, owning pets (dog, cat or both) were not significant variables of positivity for anti-T. gondii antibodies in the surveyed population. Although no significant spatial cluster was found, high intensity areas of seropositive individuals were located in the Kernel map where the suburban neighborhoods are located. In conclusion, socioeconomic vulnerability determinants may be associated to Toxoplasma gondii exposure. The increased risk due to illiteracy, adult or elderly age, unemployment and lack of household water tank were confirmed by multivariate analysis and the influence of low family income for seropositivity by the spatial analysis.